US Constitution and the Notion of Family : The risks of the Supreme Court’s judicial activism through family and privacy cases - MolnárSarolta Judit (Pázmány Law Review, 2025)
This paper examines the family and privacy jurisprudence exercised by the United States Supreme Court. These cases have provoked a substantial amount of attention from the public and politics in the history of the Court. Arguments for the decisions have been widely debated, criticized, and discussed. Arguably, some of these cases have even changed the role of the Court, the culture of the American nation, and the structure of the American society. The paper attempts to investigate these issues in detail and pose a federalist argument shedding light on the dangers of judicial activism regarding the institutions of a democratic state.